2018
DOI: 10.1108/bfj-08-2017-0466
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder responses to governmental dietary guidelines

Abstract: Purpose The purpose of this paper is to explore how stakeholders in the food and nutrition field construct and conceptualise “appropriate” national dietary advice. Design/methodology/approach In total, 40 voluntarily written stakeholder responses to updated official dietary guidelines in Sweden were analysed thematically. The analysis explored the logics and arguments employed by authorities, interest organisations, industry and private stakeholders in attempting to influence the formulation of dietary guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The Swedish process of publishing dietary guidelines is relatively open and members of the public are invited to have a say during the process. However, responses to the latest Swedish update of dietary advice (2015) came predominantly from industrial stakeholders with vested interest in influencing the guidelines (Bergman et al, 2018). The National Food Agency is known among most people and has a mostly positive public image (S. Holmberg & Tryggvason, 2014).…”
Section: The Special Case Of Trust In the Scandinavian Settingmentioning
confidence: 99%
“…The Swedish process of publishing dietary guidelines is relatively open and members of the public are invited to have a say during the process. However, responses to the latest Swedish update of dietary advice (2015) came predominantly from industrial stakeholders with vested interest in influencing the guidelines (Bergman et al, 2018). The National Food Agency is known among most people and has a mostly positive public image (S. Holmberg & Tryggvason, 2014).…”
Section: The Special Case Of Trust In the Scandinavian Settingmentioning
confidence: 99%
“…However, approximately 25% of the sample reported that they preferred neither the Healthy Food Palm nor the Saudi Healthy Plate guidelines. This may shed light on the need to include stakeholder perspectives on the concept of dietary guidelines to find “appropriate national dietary advice” [ 36 ]. Additionally, further understanding why 53.6% of respondents preferred the Saudi Healthy Plate guidelines, compared to 21.4% who preferred the Healthy Food Palm, could help identify the components of dietary guidelines that the public could more easily comprehend and adhere to.…”
Section: Discussionmentioning
confidence: 99%
“…This could be interpreted as a step away from a nutritionistic approach. Nonetheless, most FBDGs continue to employ quantification and technical terms ( Kromhout et al, 2016 ); these features of nutritionistic discourse are also endorsed by food industry and other stakeholders, both in engaging with official dietary advice and in marketing foods ( Bergman et al, 2018 ; Scrinis, 2016 ). The nutrient focused and bio-chemical aspects of food implicate important aspects of nutritional wellbeing, which remains the main purpose of FBDGs (WHO 1998).…”
Section: Introductionmentioning
confidence: 99%